Association between vitamin D status and obesity in Bulgarian pre-pubertal children: a pilot study - Galunska, Bistra T.; Gerova, Daniela I.; Galcheva, Sonya V.; Iotova, Violeta M. (International Journal of Research in Medical Sciences, 2016)
Background: It is considered that obesity and metabolic syndrome are accompanied with vitamin D deficiency. We aimed to examine the interrelations between vitamin D status and biomarkers for metabolic syndrome in Bulgarian pre-pubertal children. Methods: The study enrolled 51 pre-pubertal children (29 boys, 22 girls) examined for serum 25-xydroxyvitamin D, and routine parameters for metabolic syndrome. Obesity was evaluated by body mass index and waist circumference. Results: More than half (57.1%) of the studied children were vitamin D deficient, prevalent in girls than in boys (65.0% vs. 51.7% respectively). A tendency for worse metabolic status in the vitamin D-deficient group, expressed by higher fasting insulin, total cholesterol, total cholesterol/HDL-ratio and Homeostasis Model Assessment (HOMA)-index was observed. A trend for negative correlation was established between 25-xydroxyvitamin D and waist circumference, HOMA-index, and fasting insulin. Conclusions: Vitamin D deficiency and inverse relationships between 25-xydroxyvitamin D and waist circumference, HOMA-index, and insulin were found amongst studied children.